Historical trends in histological composition and cause specific mortality of small intestine tumors based on SEER database analysis - Tianheng Ma; Honggang Wang; Weijie Dai; Peng Shen; Jialing Zhang; Rui Xie (Scientific Reports)
Abstract Small intestine tumors, though rare, have shown a concerning increase in incidence and mortality in recent years. This study aimed to investigate the historical trends in histological composition and causes of death among patients with small intestine tumors using the SEER database. A total of 18,234 patients diagnosed with primary small intestine cancer from 1992 to 2018 were included in this study. Demographic details, tumor characteristics, treatment modalities, and outcomes were collected. Cause-specific mortality was analyzed using Fine and Gray regression, with non-small intestine-specific deaths considered as competing risks. Small intestine-specific deaths were the leading cause of mortality, with adenocarcinoma and carcinoid tumors being the most common histological types. Heart disease emerged as a significant cause of death following diagnosis, surpassing small intestine-specific deaths after 5–6 years. The study revealed variations in mortality causes across histological subtypes and identified risk factors for small intestine-specific mortality, including age, tumor site, grade, and treatment modalities. The findings highlight the substantial impact of heart disease on the long-term survival of patients with small intestine tumors. This underscores the potential benefits of adopting comprehensive management strategies that integrate oncological and cardiological care to improve survival rates and quality of life. A multidisciplinary approach in oncocardiology may help address the complex needs of these patients and optimize clinical outcomes.